An update on Cention N: An aesthetic direct bulk-fill restorative material - Alla, Rama Krishna; Medicharla, Uma Devi; Mohammed, Shammas; Abusua, Fatima; Arun Bhupathi, P; Madhu Varma, K (International Journal of Dental Materials, 2023)
The demand for aesthetic restorative materials has increased in recent years. Glass ionomer cements (GIC), their modifications, and various composite restorative materials have been developed as direct tooth-coloured restorative materials. However, none of these materials can be compared to the properties of amalgam restorative materials. Recently, a new direct tooth-coloured, bulk-fill, and aesthetic restorative material, Cention N, was developed. This material is easy to handle and has properties similar to those of type-IX GIC. This article provides an update on the composition and properties of Cention N restorative material.